A molecular diagnostic approach able to detect the recurrent genetic prognostic factors typical of presenting myeloma. Issue 2 (7th October 2014) - Boyle, Eileen M.; Proszek, Paula Z.; Kaiser, Martin F.; Begum, Dil; Dahir, Nasrin; Savola, Suvi; Wardell, Christopher P.; Leleu, Xavier; Ross, Fiona M.; Chiecchio, Laura; Cook, Gordon; Drayson, Mark T.; et al.
<x xml:space="preserve">Abstract</x> Risk stratification in myeloma requires an accurate assessment of the presence of a range of molecular abnormalities including the differing IGH translocations and the recurrent copy number abnormalities that can impact clinical behavior. Currently, interphase fluorescence in situ hybridization is used to detect these abnormalities. High failure rates, slow turnaround, cost, and labor intensiveness make it difficult and expensive to use in routine clinical practice. Multiplex ligation‐dependent probe amplification (MLPA), a molecular approach based on a multiplex polymerase chain reaction method, offers an alternative for the assessment of copy number changes present in the myeloma genome. Here, we provide evidence showing that MLPA is a powerful tool for the efficient detection of copy number abnormalities and when combined with expression assays, MLPA can detect all of the prognostically relevant molecular events which characterize presenting myeloma. This approach opens the way for a molecular diagnostic strategy that is efficient, high throughput, and cost effective. © 2014 The Authors. Genes, Chromosomes & Cancer Published by Wiley Periodicals, Inc.